DINAMIKA PSIKOLOGIS PEREMPUAN KORBAN CYBER SEXUAL HARASSMENT - Aviliani, Dita; Adnan Reza, Faisal; Isnaini, Nurul (Faculty of Ushuluddin and Humanities, 2025)
Cases of cyber sexual harassment in Indonesia continue to rise along with the growth of internet users. This research examines Cyber sexual harassment experienced by adult women and its impact on their psychology. In the digital era, although social media facilitates interaction, it also gives rise to crimes such as Cyber sexual harassment. The research method used is qualitative with a case study approach. The data collection process was carried out by observation and interviews with five female participants aged 18-25 years who had experienced cyber sexual harassment, then the data obtained was analyzed with the help of NVIVO 12 Plus software. The findings reveal that in the cognitive aspect, victims experience negative self-perception, concentration difficulties, low self-esteem, and traumatic flashbacks. In the emotional aspect, victims report feelings of shame, anxiety, fear of repeated harassment, anger, trauma, and loss of emotional control. Regarding interpersonal relationships, victims tend to withdraw, struggle to trust new people, limit social interactions, and face difficulties in forming healthy relationships. Support from close friends emerges as a crucial factor in helping victims restore self-image, overcome trauma, and regain a sense of security.